Forecasting and planning for volcanic hazards, risks, and disasters - Papale, Paolo (Hazards and disasters series, 2021)
"Forecasting and Planning for Volcanic Hazards, Risks, and Disasters expands and complements the subject and themes in Volcanic Hazards, Risks and Disasters. Together, the two volumes represent an exhaustive compendium on volcanic hazards, risks, and disasters. Volume two presents a comprehensive picture of the volcano dynamics relevant for volcanic hazard forecasts. It also includes case studies of the associated risks and aspects like operational volcano observatory responses, communication before and across volcanic crises, emergency planning, social science aspects, and resilience from volcanic disasters. Forecasting and Planning for Volcanic Hazards, Risks, and Disasters takes a geoscientific approach to the topic while integrating the social and economic issues related to volcanoes and volcanic hazards and disasters."--